WINNING THE TALENT WAR: UNDERSTANDING MALAYSIAN ISLAMIC FINANCE GRADUATE TALENTS JOB AND ORGANIZATION ATTRIBUTES PREFERENCES USING CHOICE BASED CONJOINT ANALYSIS - Adedapo Alagabi, AbdGhaffar; Abdul-Majid, Abdul-Halim; Rashid, Rosemaliza (International Journal of Engineering Technologies and Management Research, 2017)
The talent crunch and consequent war of talent poses serious risk for the success and sustainability of industries all over the globe. This is most especially so in the Malaysian Islamic finance industry which has been witnessing huge talent gap and fierce competition for limited talent. This study, unlike past research, employs discrete choice conjoint analysis, a new quantitative method to provide information on the relative importance of identified job and organisation attributes in determining the job preference or choice of graduate talents of Insaniah university college Malaysia. All identified job and organisation attributes were found to positively significant in determining job choice of talents. Job security is relatively the most preferred attribute and donation to charity is the least preferred. Organization reputation attributes such as training and development which are internal reputation attributes are found to be relatively very important. In contrast, donation to charity, an external corporate reputation attribute, is found to be least relatively important. This study results strongly suggest that policy makers in Malaysian Islamic finance industry should incorporate the preferred attributes in the employee value proposition to attract the needed pool of talent.